Stock liquidity, stock price crash risk, and foreign ownership - Ozge Sezgin Alp; Bilge Canbaloglu; Gozde Gurgun (Borsa Istanbul Review, 2022)
This study examines the impact of stock market liquidity on a stock price crash, using firm data from Borsa Istanbul for the period 2009–2019. The results show that higher stock liquidity increases the likelihood of stock price crashes, but this positive link is not driven by blockholder ownership. The study also investigates the effects of foreign investors, divided between institutional and individual investors, on the relation between liquidity and crash risk. The findings indicate that higher stock liquidity increases the crash risk as the share of foreign institutional investor rises, but this impact is not present with foreign individual participation. Furthermore, the study explores the effects of high-frequency trading and the removal of short-sale restrictions. The results of these analyses suggest that high-frequency trading increases liquidity, which in turn raises the likelihood of a stock price crash, and the removal of short-sale restrictions generally increases the stock price crash risk.